The Investigation of Safety Climate Using Nordic Safety Climate Questionnaire (Nosacq-50): A Case Study at A Paper Industry - Rahdiana, Nana; Suhara, Ade; Hakim, Afif; Hartono, Markus (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 10 No 01 (2024): Volume 10 No 01 Tahun 2024, 2024)
The pulp and paper industry is one of the industries that significantly contributes to the national economy. Indonesia has at least 103 companies in the paper industry sector, with a total paper production capacity of 18.26 million tons per year. The industry has employed 1.36 million workers and generated exports worth USD 7.5 billion in 2021. The paper industry is not only categorized as a labor-intensive industry but also as a high-risk industry. This study aims to analyze the safety climate in the production department of the paper industry in West Java Province, Indonesia. This study involved the participation of 366 individuals in different roles, including managers, supervisors, leaders, officers, and operators, who were interviewed and asked to complete a questionnaire using the NOSACQ-50 method. The NOSACQ-50 method consists of 7 dimensions of safety climate. The results show that all safety climate dimensions scored between 3.38-3.77, which is a perfect level that needs to be maintained and continuously improved. The safety climate score of the paper industry in Indonesia has a similar pattern to the previous research results released by Nordic on its official website but with higher values. The results of this study are consistent with previous research, which posits safety climate as a homogeneous shared perception characteristic of an organization's safety culture.